2000
DOI: 10.1007/bf03391995
|View full text |Cite
|
Sign up to set email alerts
|

Private events: Do they belong in a science of human behavior?

Abstract: The role of thinking, feeling, and other private events has received a great deal of attention in mainstream psychology but has been virtually ignored in behavior analysis until recently. This paper introduces a series of papers from a symposium that explored the roles of private events in a science of human behavior. We briefly explore the role private events are assigned in several behavioral orientations. Next, we discuss several positions on how private events might be conceptualized within a behavior-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
24
0
2
Order By: Relevance
“…(E-mail: okouchi@cc.osaka-kyoiku .ac.jp). Freeman, & Scotti, 2000). Methodological behaviorism defines psychology as the study of behaviors that are observable by others (e.g., Guthrie & Horton, 1946, p. 7), whereas cognitive behaviorism allows the study of events unobservable by others as intervening variables (Bandura, 1977;Mahoney, 1977).…”
mentioning
confidence: 99%
“…(E-mail: okouchi@cc.osaka-kyoiku .ac.jp). Freeman, & Scotti, 2000). Methodological behaviorism defines psychology as the study of behaviors that are observable by others (e.g., Guthrie & Horton, 1946, p. 7), whereas cognitive behaviorism allows the study of events unobservable by others as intervening variables (Bandura, 1977;Mahoney, 1977).…”
mentioning
confidence: 99%
“…That is, evidence has demonstrated that individuals with disabilities have varying language abilities and experience private events that may influence behavior (Reid et al 2011). Further, behavior analysts have encouraged more consideration of private events in treatment (Anderson et al 2000;Friman et al 1998;Moore 2000). Finally, ACT may be an appropriate approach because it is conceptually systematic with and grounded in the assumptions and principles of behavior analysis.…”
Section: Acceptance and Commitment Therapymentioning
confidence: 99%
“…However, traditional behavior analytic (i.e., function-based) interventions tend not to take the client's language and private events into account when assessing and treating behavior. Some behavior analysts would argue that this may be problematic, based on the knowledge that private events are behavior that can further affect other behaviors (Anderson et al 2000;Friman et al 1998;Moore 2000). Over the past two decades, several behavior analysts have called for broader consideration of the role of private events in behavior analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior analysts have been using the concept of establishing operations (eo) for over 50 years (e.g., Dougher & Hackbert, 2000;Keller & Schoenfeld, 1950;leigland, 1984;Michael, 1982), but few empirical studies continue the topic beyond those of deprivation and aversive stimulation (Anderson, Hawkins, Freeman, & Scotti, 2000;Dougher & Hackbert, 2000). Process accounts of eos (particularly conditioned eos) remain speculative and largely untested empirically.…”
mentioning
confidence: 99%